1975
DOI: 10.1037/h0077430
|View full text |Cite
|
Sign up to set email alerts
|

Role of monoamines in the control of hormones of sexual receptivity in the female rat.

Abstract: The involvement of indole-and catecholamines in the hormonal regulation of sexual receptivity has been investigated in ovariectomized female rats. Drugs that reduce 5-hydroxytryptamine, dopamine, and adrenaline or increase noradrenaline neurotransmission tended to facilitate the occurrence of estrous behavior in estrogen-treated females, and drugs having opposite effects tended to inhibit receptivity induced by estrogen and progesterone. Estrogen decreased noradrenaline turnover in cortex and brain stem; proge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
1

Year Published

1979
1979
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(53 citation statements)
references
References 65 publications
4
48
1
Order By: Relevance
“…Although all D1-agonists enabled reproductive behavior in the present study, the more efficacious SKF85174 proved to be significantly more inhibitory than the less potent, weak agonists SKF38393 and SKF77434. This finding is consistent with previous studies (Everitt et al, 1975;Foreman and Moss, 1979;Grierson et al, 1988) in which the effects of SKF38393 were reported. Interestingly, animals treated with SKF75670, a D1-like agonist with little if any cyclase activity in rat striatal tissue, displayed stimulation of behavior at all doses.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Although all D1-agonists enabled reproductive behavior in the present study, the more efficacious SKF85174 proved to be significantly more inhibitory than the less potent, weak agonists SKF38393 and SKF77434. This finding is consistent with previous studies (Everitt et al, 1975;Foreman and Moss, 1979;Grierson et al, 1988) in which the effects of SKF38393 were reported. Interestingly, animals treated with SKF75670, a D1-like agonist with little if any cyclase activity in rat striatal tissue, displayed stimulation of behavior at all doses.…”
Section: Discussionsupporting
confidence: 94%
“…The present results support previous studies (Everitt et al, 1975;Everitt and Fuxe, 1977;Foreman and Moss, 1979;Grierson et al, 1988;Mani et al, 1994) indicating that third ventricle administration of dopamine or the selective D1-like agonist SKF38393 facilitates receptivity and extends previous findings to three analogs of SKF38393. In vitro, the four D1-like agonists used in this study possess different relative efficacies [compared with dopamine (100 mM)] for stimulating adenylyl cyclase in rat striatal tissue (Andersen and Jansen, 1990;Undie and Friedman, 1992).…”
Section: Discussionsupporting
confidence: 92%
“…As to in vivo studies, although there are several reports (at least seven) that analyze the actions of E 2 on serotonergic reuptake sites, the results are inconclusive. Thus increases, decreases, and nochange on the serotonergic transporter are all reported (Attali et al, 1997;Cardinali and Gómez, 1977;Everitt et al, 1975;McQueen et al, 1997;Mendelson et al, 1993;Rehavi et al, 1987;Wilson et al, 1988). It is possible that the discrepancies could rely on variables such as the time elapsed between ovariectomy and estrogen treatment, the duration of estrogen treatment (acute vs chronic), the type of ligands used, and the site of the brain evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the activation of progesterone receptors in sexually receptive females is known to inhibit sexual receptivity (Reading and Blaustein, 1984). Given that motivated behaviors, such as sexual behavior and drug-taking behavior, are mediated by overlapping neural systems (Everitt et al, 1974(Everitt et al, , 1975Kelley and Berridge, 2002), including DA systems (Mermelstein and Becker, 1995;Pfaus et al, 1990;Phillips et al, 1991;Vezina, 1993), perhaps it is not surprising that progesterone has inhibitory effects on cocaine self-administration behavior. Furthermore, several recent publications have postulated that progesterone attenuates cocaine-induced behavioral activation (Sell et al, 2000;Russo et al, 2003;Festa and Quinones-Jenab, 2004); however, this is the first study to demonstrate that progesterone inhibits cocaine-taking behavior in rats.…”
Section: Relevance To Existing Literaturementioning
confidence: 99%